Antigen-Specific Immune Tolerance in Multiple Sclerosis—Promising Approaches and How to Bring Them to Patients - Lutterotti, Andreas; Hayward-Koennecke, Helen; Sospedra, Mireia; Martin, Roland (Frontiers in Immunology, 2021)
Antigen-specific tolerance induction aims at treating multiple sclerosis (MS) at the root of its pathogenesis and has the prospect of personalization. Several promising tolerization approaches using different technologies and modes of action have already advanced to clinical testing. The prerequisites for successful tolerance induction include the knowledge of target antigens, core pathomechanisms, and how to pursue a clinical development path that is distinct from conventional drug development. Key aspects including patient selection, outcome measures, demonstrating the mechanisms of action as well as the positioning in the rapidly growing spectrum of MS treatments have to be considered to bring this therapy to patients.